Knowledge of Healthcare Professionals Regarding Hepatitis B in Rania Hospitals - Raouf Ali, Zhino; Rasol Ahmed, Mohammed; Muhamad Hamad, Khalid; Hussen Wsu, Zhiar (Kurdistan Journal of Applied Research, 2020)
Hepatitis B virus (HBV) infection is a major public health problem worldwide especially for healthcare professionals (HCPs). It is a potentially life-threatening condition because leads to liver infection, and liver cancer. There is a shortage of research on undergraduate students. The main aim of this study was conducted to assess the level of knowledge of health care professionals regarding HBV at Rania hospitals in the Kurdistan region of Iraq during the period of 20th October 2019 to 16th April 2020. Non- probability purposive sample of (303) HCPs; for data collection, the study instrument was constructed and designed through reading literature, books, and articles which included (42) items. Reliability of the instrument was determined through the use of stability reliability (test and retest) approach which was estimated as r = (0.83.)The data were collected through the use of the interview technique then organized and coded into computer files. Statistical approaches were uses for data analysis, which includes: descriptive and inferential statistics and chi-square, data analysis (SPSS version 25). The results indicated that the majority of the study samples were in the age group (? 30)) years and the female participants was more than male, three-quarters of the participants were married, most of them were graduated from institute nursing and less than half of HCPs had 6-10 years of employment, but the majority of the participants were not trained at all, and most of them had not immunized against HBV vaccine. Three-quarters of HCPs had moderate knowledge regarding HBV infection. Also, the current study demonstrated a significant association between the educational level and HCP’s knowledge regarding HBV, at a P value less than 0.05. on site other hand, there was no significant association between HCP’s age, gender, marital status, years of employment, and training course concerning hepatitis with the level of knowledge regarding HBV. The researchers recommended to the ministry of health and directorate of health in Rania city to complete vaccinate against HBV for all HCPs and participating their staff in healthy scientific issues and symposiums.